2014 47th Hawaii International Conference on System Sciences 2014
DOI: 10.1109/hicss.2014.620
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Software Product Innovation Assessment by Using a Systematic Literature Review

Abstract: Innovation is a driver of global economy growth. Software intensive systems (SiSs) are embedded in the systems of various leading sectors, such as the automotive, robotics, and mobile phone industries and they are creating new opportunities for innovation. However, SiSs are affected by a rapidly changing market and a reduced time to market. Software product innovation assessment is becoming important because firms need to know as soon as possible if their products are aligned with the market and customer deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In the software engineering domain, our previous work found several systematic literature reviews have been performed to aggregate different aspect of innovation (Edison et al, 2016). Through a systematic review, Yagüe et al (2014) reported the existing assessment schemes applicable to software product innovation. In addition, Munir et al (2015) presented a review on open innovation.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In the software engineering domain, our previous work found several systematic literature reviews have been performed to aggregate different aspect of innovation (Edison et al, 2016). Through a systematic review, Yagüe et al (2014) reported the existing assessment schemes applicable to software product innovation. In addition, Munir et al (2015) presented a review on open innovation.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The assessment criteria are from the critical appraisal skills programme (CASP) for qualitative assessment [32]. Based on the CASP, we set the following questions for this assessment [30]: i) is there a clear statement of the aims and objectives of the research? ; ii) is there an adequate description of the context in which the research was carried out?…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of this exploratory job was to identify if a model for software intensive systems innovation assessment had been developed, or, otherwise, if software intensive systems innovation characteristics had been assessed using a general purpose model. What was found as a result of the SLR performed and already reported in [117], is that no specific assessment model was available for Software intensive Systems. At this stage of the research the decision made was to carry on the job of analysing existing innovation assessment models, available in literature, usually non-specific to a concrete industry, to identify model elements, or even the better building a reference model that could be the basis to assess software intensive systems.…”
Section: Overall Strategymentioning
confidence: 96%
“…This tool called Product Innovation Assessment Tool (PIA-Tool) is still under development that is, PIA-Tool will cover the whole process, but in the scope of this thesis it includes the implementation of the assessment questionnaires representation to provide a support for data gathering, and then the application of these collected data to positioning the product from the innovation perspective. Even considering that there is no agreement whether factors should be qualitative or quantitative, in this thesis and based on the findings obtained in the SLR performed [117], we decided to use qualitative values to represent innovation factors because data collection with these type of data is simpler for survey respondents than quantitative data. Following the recommendations of Tsai [103], factors are represented by discrete values and the criterion scale proposed is VP: Very Poor, P:Poor, F: Fair, G: Good and VG: Very Good.…”
Section: The Assessment and Positioning Systemmentioning
confidence: 99%
See 1 more Smart Citation